Correlation between Cranial Base, Mandible, and Hyoid Bone Position in Different Anteroposterior Skeletal Malocclusions: A Cephalometric Study - Sadik, Jaffer; Shetty, Akhil (Journal of Health and Allied Sciences NU, 2023)
Background Development of malocclusion can be promptly recognized through an understanding of the optimal position of the bone structures in the orofacial system and their relationship to the cranial base and jaw base. The aim of this study was to assess the relationship between the cranial base, mandible, and hyoid bone in different anteroposterior skeletal malocclusions.Materials and Methods This retrospective study evaluated 120 lateral cephalometric radiographs of individuals aged between 15 and 30 years. The subjects were classified using Burstone's analysis into three groups based on the N perpendicular to point A and N perpendicular to point B. The collected lateral cephalograms of the selected individuals were analyzed using Nemoceph v.12 software (Nemotec, Spain). The nasion-sella-articulare (NSAr), hyoidale angle (C3HyD), sella-articulare-hyoid angle (SArHy), and nasion-sella-hyoid (NSHy) angles were measured and compared among all the three groups.Results In the present study, considering the various angles among the three study groups, a statistically significant difference was observed for the SArHy angle (p < 0.05). However, the saddle angle (NSAr) and hyoidale angle (C3HyD) showed no statistically significant difference between the three study groups. Post hoc Bonferroni test was applied to compare the differences between two groups. A statistically significant difference (p < 0.05) was observed between class I and class II and between class II and class III groups.Conclusion Though the findings of the present study concluded that there is no variation in saddle angle among the three groups, the significant association of SArHy angle among class I, class II, and class III skeletal relationships, suggests an adaptation of the hyoid bone position in various skeletal patterns. We also suggest that the posterior positioning of the hyoid bone is related to skeletal class II malocclusion, whereas a forward positioning of the hyoid bone is related to skeletal class III malocclusion.
Keywords: cranial base; mandible; hyoid bone; saddle angle; malocclusion